1998
DOI: 10.1177/00220345980770101101
|View full text |Cite
|
Sign up to set email alerts
|

Bite Forces with Mandibular Implant-retained Overdentures

Abstract: Sensitivity or pain of the mucoperiosteum covering the mandibular edentulous ridge is often thought to limit bite forces in complete-denture wearers. Therefore, bite forces with mandibular implant-retained overdentures may depend on the degree of implant support. This study analyzed the effects of different degrees of support for the mandibular denture on bite forces measured four years after denture treatment as part of a randomized controlled clinical trial. All subjects had received new maxillary dentures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
131
2
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(156 citation statements)
references
References 18 publications
14
131
2
9
Order By: Relevance
“…The stress distribution, areas of stress concentration, minimum and maximum principal stress and displacement at certain points were compared with that of an intact mandible as control, when loaded with a static load of 300 N at the incisor region. This simulates the bite force of an average patient (Van Eijden, 2000;Marunick et al, 1992;Curtis et al, 1999;Maurer et al, 2006;Fontijn-Tekamp et al, 1998). Variations were then made to the defect and stem sizes to look at any changes to the stress distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The stress distribution, areas of stress concentration, minimum and maximum principal stress and displacement at certain points were compared with that of an intact mandible as control, when loaded with a static load of 300 N at the incisor region. This simulates the bite force of an average patient (Van Eijden, 2000;Marunick et al, 1992;Curtis et al, 1999;Maurer et al, 2006;Fontijn-Tekamp et al, 1998). Variations were then made to the defect and stem sizes to look at any changes to the stress distribution.…”
Section: Introductionmentioning
confidence: 99%
“…However, our results demonstrate the feasibility of measuring the activated areas in the primary sensorimotor cortex during clenching using fMRI, which revealed that the brain activity is related to the magnitude of the bite force. Therefore, oral rehabilitation with prosthetic treatment, which increases the bite force, [17] not only improves the chewing efficacy but also affects the brain in a positive manner; potentially, the improved bite force may prevent brain degeneration. Additional studies comparing the brain activity before and after prosthetic treatment in edentulous subjects are recommended to evaluate the neurophysiologic effect of prosthetic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…25 A number of parameters have been used to categorize vertical facial type, including the cant of the mandibular plane, 26 cant of the palatal plane, 27 and ratios of anterior and posterior face heights. 26 In this study, maxillomandibular planes angle, facial height, and dental overbite were used to categorize the facial form.…”
Section: Discussionmentioning
confidence: 99%